2020
DOI: 10.1177/0894439320979951
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Surveys With Data From Sensors and Apps: Opportunities and Challenges

Abstract: The increasing volume of “Big Data” produced by sensors and smart devices can transform the social and behavioral sciences. Several successful studies used digital data to provide new insights into social reality. This special issue argues that the true power of these data for the social sciences lies in connecting new data sources with surveys. While new digital data are rich in volume, they seldomly cover the full population nor do they provide insights into individuals’ feelings, motivations, and attitudes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…There are various sensors that can be used in a smartphone: multiple location-based sensors (GPS, gyroscopes), accelerometers, audio sensors, Bluetooth radios, Wi-Fi antennas, and with the advancement of technology, many other sensors–such as pulse or blood pressure sensors. In the field of healthcare, such passive data collection is becoming the main solution for health monitoring in the elderly or in other special scenarios [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are various sensors that can be used in a smartphone: multiple location-based sensors (GPS, gyroscopes), accelerometers, audio sensors, Bluetooth radios, Wi-Fi antennas, and with the advancement of technology, many other sensors–such as pulse or blood pressure sensors. In the field of healthcare, such passive data collection is becoming the main solution for health monitoring in the elderly or in other special scenarios [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing use of smartphones for web surveys also facilitates novel ways to collect additional data, such as sensor data. Smartphones have a variety of built-in sensors, such as Global Positioning System (GPS) and accelerometer, which have the potential to augment and extend respondents' answers (Struminskaya et al 2020). In other words, the data collected from or via smartphone sensors may help researchers to supplement survey data with additional measures.…”
Section: Discussionmentioning
confidence: 99%
“…It also makes the communication process between researchers and respondents more natural by simulating daily conversation. Because audio and voice communication channels gain importance in everyday life (e.g., in the form of virtual assistant technology; see Struminskaya, Lugtig, Keusch, & Höhne, 2020), it seems worthwhile to investigate their usefulness and usability for web survey research as well. Following Conrad et al (2017), giving respondents the choice to select the communication channel that is most suitable for them may enhance survey data quality (see also Miller (2017) for a comprehensive discussion of the future of surveys).…”
Section: Background and Research Questionsmentioning
confidence: 99%
“…This trend has also been detected in the German Respondi online access panel (Gummer et al, 2019), in commercial and academic surveys in the US and several other countries, such as the Netherlands and Spain (Peterson et al, 2017), and in surveys of the Netquest online access panel in Argentina, Brazil, Chile, Colombia, Mexico, Portugal, and Spain . Given that answering a web survey on a smartphone differs from answering it on a PC due to device characteristics, such as screen size and operation, a variety of studies have investigated how the use of different devices affects survey data quality (see, for example, Couper & Peterson, 2017;de Bruijne & Wijnant, 2013;Krebs & Höhne, 2021;Lugtig & Toepoel, 2016;Mavletova, 2013;Struminskaya, Lugtig, Keusch, & Höhne, 2020;Wells, Bailey, & Link, 2014). For example, these studies have found that smartphone respondents are more likely to drop out of a survey (Callegaro, 2010;Poggio, Bosnjak, & Weyandt, 2015) and need longer to complete it (Antoun, Couper, & Conrad, 2017;Couper & Peterson, 2017;Gummer & Roßmann, 2015) than PC respondents.…”
Section: Introductionmentioning
confidence: 99%